Novel Secreted Protein of Mycoplasma bovis MbovP280 Induces Macrophage Apoptosis Through CRYAB - Zhao, Gang; Zhu, Xifang; Zhang, Hui; Chen, Yingyu; Schieck, Elise; Hu, Changmin; Chen, Huanchun; Guo, Aizhen (Frontiers in Immunology, 2021)
Mycoplasma bovis causes important diseases and great losses on feedlots and dairy farms. However, there are only a few measures to control M. bovis-related diseases. As in other mycoplasma species, this is predominantly because the virulence related factors of this pathogen are largely unknown. Therefore, in this study, we aimed to identify novel virulence-related factors among the secreted proteins of M. bovis. Using bioinformatic tools to analyze its secreted proteins, we preliminarily predicted 39 secreted lipoproteins, and then selected 11 of them for confirmation based on SignalP scores > 0.6 or SceP scores > 0.8 and conserved domains. These 11 genes were cloned after gene modification based on the codon bias of Escherichia coli and expressed. Mouse antiserum to each recombinant protein was developed. A western blotting assay with these antisera confirmed that MbovP280 and MbovP475 are strongly expressed and secreted proteins, but only MbovP280 significantly reduced the viability of bovine macrophages (BoMac). In further experiments, MbovP280 induced the apoptosis of BoMac treated with both live M. bovis and MbovP280 protein. The conserved coiled-coil domain of MbovP280 at amino acids 210–269 is essential for its induction of apoptosis. Further, immunoprecipitation, mass spectrometry, and coimmunoprecipitation assays identified the anti-apoptosis regulator αB-crystallin (CRYAB) as an MbovP280-binding ligand. An αβ-crystallin knockout cell line BoMac-cryab−, Mbov0280-knockout M. bovis strain T9.297, and its complemented M. bovis strain CT9.297 were constructed and the apoptosis of BoMac-cryab− induced by these strains was compared. The results confirmed that CRYAB is critical for MbovP280 function as an apoptosis inducer in BoMac. In conclusion, in this study, we identified MbovP280 as a novel secreted protein of M. bovis that induces the apoptosis of BoMac via its coiled-coil domain and cellular ligand CRYAB. These findings extend our understanding of the virulence mechanism of mycoplasmal species.